TECHNICAL EFFICIENCY DETERMINANTS OF OECD COUNTRIES’ AGRICULTURAL PRODUCTION - A STOCHASTIC FRONTIER ANALYSIS APPROACH - Saeid HAJIHASSANIASL (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The purpose of this study is to analyze the efficiency in OECD countries’ agricultural sector and also to examine some selected factors that affecting the efficiency of production in this sector. For this aim, using Stochastic Frontier Analysis (SFA) during the period 2015-2019, the agricultural producers’ technical efficiency in all 38 OECD member countries was evaluated. However, some factors affecting efficacy in these countries were also examined. According to the study’s results, the average technical efficiency value in the agricultural sector of OECD countries in the 2015-2019 period was 78.6%. The countries with the lowest and highest average technical efficiency were Luxembourg and Colombia, respectively. On the other hand, as a result of the examination of the factors affecting the efficiency in these countries, it was revealed that the Global Innovation Index variable did not affect the efficiency of agricultural producers, but the reel exchange rate and agricultural pesticide use variables positively affected the efficiency.